THE SIGNIFICANCE OF SUFI MUSIC IN CONTEMPORARY CULTURAL LIFE - Ergashov Abbos Baxridinovich (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2026)
This article examines the importance of Sufi music in contemporary cultural life, focusing on its spiritual, aesthetic, and social functions in the modern world. It explores how Sufi musical traditions continue to influence cultural identity, promote spiritual reflection, and foster intercultural dialogue in an increasingly globalized society. The study highlights the adaptability of Sufi music, demonstrating how its core spiritual values are preserved while engaging with modern artistic forms and audiences. By analyzing contemporary performances, festivals, and cultural practices, the research underscores the enduring relevance of Sufi music as a source of spiritual inspiration and cultural continuity.